Recommended improvements for online learning based on Omani students’ experiences and perspectives - AL-Busaidi, Zakiya Nasser; Rajesh, Preethy (International Journal of Evaluation and Research in Education (IJERE), 2025)
The outbreak of COVID-19 prompted a worldwide transition to online education in academic institutions, which had a profound effect on both instructors and learners. This study aims to investigate the perspectives and experiences of students who have undergone emergency remote learning at the University of Technology and Applied Sciences (UTAS) in the Nizwa branch. The study explored students’ experiences in four areas: i) the impact of online learning on academic performance, learning skills, communication, health, and motivation; ii) students’ preferences; iii) the challenges they faced; and iv) the suggestions they have for enhancing the online learning environment. An online survey was conducted with 447 students, and the data collected were analyzed both quantitatively and qualitatively. This study shows that online learning has impacted students’ academic performance, communication, health, and motivation. The findings revealed that students preferred live online lectures and exams but were dissatisfied with the online learning system overall. Content analysis revealed that the most significant challenges faced by students were technical issues, study-related concerns, and learning difficulties. These findings highlight the necessity of enhancing the infrastructure, fostering communication, and implementing effective teaching methods to create a more engaging and productive online learning environment.